Constructing 'exceptionality': a neglected aspect of NHS rationing. Issue 8 (20th June 2019) - Hughes, David; Doheny, Shane
Abstract: In the British NHS the principle of exceptionality involves assessing whether a patient is sufficiently different from the generality of patients to justify providing a treatment, such as an expensive cancer drug, not approved for routine funding. In England, individual requests for certain high‐cost treatments are considered by local panels that examine exceptionality alongside treatment efficacy and cost as the main criteria for funding. This was also the case in Wales until September 2017. Our paper draws on audio recordings of panel meetings and interviews in a Welsh Health Board to investigate how exceptionality was constructed in discussions. It focuses on the problematic combination of different decision criteria in meeting talk, particularly regarding the discourses associated with efficacy and exceptionality. Exceptionality is a fluid category that raised questions about the evidence‐based nature of panel decision making. In particular, the paper discusses the use of subgroup data from RCTs and the difficulty of deciding how small a subgroup of patients should be before it is deemed exceptional. Determining exceptionality has been an important mechanism for deciding that a minority of NHS patients can still receive high‐cost treatments not routinely provided for all. As a neglected rationing mechanism it warrants sociological examination.